Perancangan Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Terbaik pada PT XYZ menggunakan Metode TOPSIS - Muhammad Reyza Nirwana; Desi Pibriana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
PT XYZ is a company in the field of construction, development, and management of construction projects. They are responsible for planning, managing, and implementing construction projects, both for infrastructure and commercial buildings. The previous assessment did not have a weighting of the criteria assessment and took time to process the value of each employee because the assessment still used a manual method (assisted by calculator calculations) so that the employee calculation process was processed one by one. This is not in accordance with the director's expectations and has an impact on the assessment being inaccurate and detrimental to the company in terms of time. Therefore, to evaluate the performance of top employees at PT XYZ, this decision support system application was created, with the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method which can produce a simple Decision Support System with an easy-to-understand and logical concept in the PT XYZ Employee Performance Assessment.